2019
DOI: 10.1111/aor.13513
|View full text |Cite
|
Sign up to set email alerts
|

Accumulations of von Willebrand factor within ECMO oxygenators: Potential indicator of coagulation abnormalities in critically ill patients?

Abstract: Clot formation within membrane oxygenators (MOs) remains a critical problem during extracorporeal membrane oxygenation (ECMO). The composition of the clots—in particular, the presence of von Willebrand factor (vWF)—may be an indicator for prevalent nonphysiological flow conditions, foreign body reactions, or coagulation abnormalities in critically ill patients. Mats of interwoven gas exchange fibers from randomly collected MOs (PLS, Maquet, Rastatt, Germany) of 21 patients were stained with antibodies (anti‐vW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 42 publications
(97 reference statements)
2
42
2
Order By: Relevance
“…VA-ECMO is more likely than VV-ECMO to cause thrombocytopenia. This is related to platelet consumption due to athrombus caused by membrane oxygenator-induced vWF aggregation [203]. The duration of ECMO is largely unrelated to thrombocytopenia [204].…”
Section: Preventionmentioning
confidence: 99%
“…VA-ECMO is more likely than VV-ECMO to cause thrombocytopenia. This is related to platelet consumption due to athrombus caused by membrane oxygenator-induced vWF aggregation [203]. The duration of ECMO is largely unrelated to thrombocytopenia [204].…”
Section: Preventionmentioning
confidence: 99%
“…Identified plasma proteins included fibrin [ 11 , 12 ], von Willebrand factor (vWF) [ 13 , 14 , 15 ] and other plasma proteins [ 13 , 16 ] as well as blood cells, which included erythrocytes [ 11 , 12 ], leukocytes [ 14 , 15 , 17 ], platelets [ 11 , 12 , 15 ] and progenitor cells [ 17 ]. Five of the seven studies utilized immunofluorescent techniques (e.g., flow cytometry, fluorescence microscopy, western blotting) to label specific blood components that adhered to the circuit [ 11 , 13 , 14 , 15 , 17 ]. One study used two-dimensional (2-D) electrophoresis as a method for the identification of specific blood components [ 16 ] whilst two studies implemented scanning electron microscopy (SEM) to visualize biomass accumulations.…”
Section: Resultsmentioning
confidence: 99%
“…However, in three of the seven studies, the identification of the blood components bound to the ECMO circuit were not the main aim of the studies. Wilm et al [ 14 ] and Steiger et al [ 15 ] observed ECMO oxygenator accumulations as potential predictors for coagulation abnormalities whilst Lehle et al [ 11 ] identified surface deposits as indicators for increased blood flow resistance in ECMO circuits. These articles were therefore limited in terms of the detail that was specified in relation to the ECMO circuit adsorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al [61] reported that the rate of thrombocytopenia in patients receiving ECMO is as high as 83%. VA-ECMO is more likely than VV-ECMO to cause thrombocytopenia, because of platelet consumption caused by membrane oxygenator induced vWF aggregation [62]. The incidence of HIT can reach 20% during ECMO.…”
Section: Preventionmentioning
confidence: 99%